2016
DOI: 10.1002/etep.2171
|View full text |Cite
|
Sign up to set email alerts
|

New approach for the modeling of induction machines operating under unbalanced power system

Abstract: In this paper, a new analytical method for the modeling of the star connected induction motors operating under unbalanced power supply is developed using coupled circuits theory. This method takes into account the increase of the common point voltage during unbalanced supply conditions. The equations, which describe the state model as well as the calculation of machine inductances, are presented. The calculation of inductances is based on the magnetomotive force distribution through the machine air-gap. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Also, it can be concluded that analytical solution for induction machine speed-time curve (A) (B) during direct start-up can be used for transient and stability studies (for example, the impact of induction machine start on the voltage drop, voltage sags, and similar). It should be noted that the importance of induction machine model in power system stability studies is analyzed in Brucoli et al, 35 while the importance of modeling and simulation of unsymmetrical supplied three-phase induction motor (for example-start-up of the unsymmetrically supplied induction motor) is presented in Zuckerberger and Alexandrovitz 36 and Kouchih et al 37 6 | CONCLUSION In this paper, an analytical solution for induction machine speed determination during direct start-up is developed in terms of the Lambert W function. The proposed solution is based on machine data, which are generally given by manufacturers or can be obtained by using some of literature-based methods or basic tests.…”
Section: Methods For Solving Lambert W Functionmentioning
confidence: 99%
“…Also, it can be concluded that analytical solution for induction machine speed-time curve (A) (B) during direct start-up can be used for transient and stability studies (for example, the impact of induction machine start on the voltage drop, voltage sags, and similar). It should be noted that the importance of induction machine model in power system stability studies is analyzed in Brucoli et al, 35 while the importance of modeling and simulation of unsymmetrical supplied three-phase induction motor (for example-start-up of the unsymmetrically supplied induction motor) is presented in Zuckerberger and Alexandrovitz 36 and Kouchih et al 37 6 | CONCLUSION In this paper, an analytical solution for induction machine speed determination during direct start-up is developed in terms of the Lambert W function. The proposed solution is based on machine data, which are generally given by manufacturers or can be obtained by using some of literature-based methods or basic tests.…”
Section: Methods For Solving Lambert W Functionmentioning
confidence: 99%
“…In this context, the aim of this paper is to demonstrate with several examples that the use of slightly asymmetrical windings can be a reasonable choice and, in certain cases, a favorable option during the design stage of electrical machines like IPMSMs, which require proper design, modeling, and control accuracy …”
Section: Introductionmentioning
confidence: 99%
“…9,10 In this context, the aim of this paper is to demonstrate with several examples that the use of slightly asymmetrical windings can be a reasonable choice and, in certain cases, a favorable option during the design stage of electrical machines like IPMSMs, which require proper design, modeling, and control accuracy. [11][12][13][14][15][16][17][18][19] More in detail, by considering an IPMSM (named IPMSM-A) equipped with a 3-phase symmetrical winding as a reference structure, the corresponding star of slots is determined by adopting Tingley's scheme. Then, this motor geometry is analyzed by using a finite element method (FEM) approach, to determine both the generated cogging torque and the torque/load angle characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To be able to reduce the MMF harmonics, some other studies have been proposed different methods such as adopting asymmetrical windings, applying a new vector control schema observing the back electromotive force (back‐EMF) waveform, and adopting axial flux modular structure with straight slots and concentrated windings . The importance and effect of MMF harmonics on the performance characteristics of various machines form induction machine to reluctance machine has also been emphasized …”
Section: Introductionmentioning
confidence: 99%
“…22 The importance and effect of MMF harmonics on the performance characteristics of various machines form induction machine to reluctance machine has also been emphasized. 23,24 In this study, influence of FSCWs on the electromagnetic and thermal performance of an IPM machine, designed by using the same specifications as Toyota Prius 2010 IPM machine, has been investigated. It has been validated that the significantly high level of MMF harmonics causes an increase in the rotor losses.…”
mentioning
confidence: 99%